Immunofluorescence-guided atomic force microscopy to measure the micromechanical properties of the pericellular matrix of porcine articular cartilage - Wilusz, Rebecca E. (The Royal Society, 2012)
The pericellular matrix (PCM) is a narrow region that is rich in type VI collagen that surrounds each chondrocyte within the extracellular matrix (ECM) of articular cartilage. Previous studies have demonstrated that the chondrocyte micromechanical environment depends on the relative properties of the chondrocyte, its PCM and the ECM. The objective of this study was to measure the influence of type VI collagen on site-specific micromechanical properties of cartilage in situ by combining atomic force microscopy stiffness mapping with immunofluorescence imaging of PCM and ECM regions in cryo-sectioned tissue samples. This method was used to test the hypotheses that PCM biomechanical properties correlate with the presence of type VI collagen and are uniform with depth from the articular surface. Control experiments verified that immunolabelling did not affect the properties of the ECM or PCM. PCM biomechanical properties correlated with the presence of type VI collagen, and matrix regions lacking type VI collagen immediately adjacent to the PCM exhibited higher elastic moduli than regions positive for type VI collagen. PCM elastic moduli were similar in all three zones. Our findings provide further support for type VI collagen in defining the chondrocyte PCM and contributing to its biological and biomechanical properties.